The effect of COVID-19 pandemic restrictions on the frequency of diabetic ketoacidosis at the time of diagnosis in children with type 1 diabetes - Esen, Ihsan; Kocaman, Selami; Acar, Nurdan Yildirim; Paksoy, Firdevs Dilara; Okdemir, Deniz (Karger, 2023)
[Abstract Not Available]